A numerical investigation of the interaction between interlaminar and intralaminar damages in a fatigued composite panel. Issue 5 (8th February 2023) - Russo, Angela; Palumbo, Concetta; Riccio, Aniello
Abstract: The fatigue behavior of composite materials is still a very challenging issue for the scientific community. So far, several numerical methodologies allow us to faithfully simulate the propagation of delamination due to fatigue. However, the reduction of material properties due to the applied cyclic load should be considered. The main objective of this work is to investigate the role of the material property degradation and the intralaminar damages on the propagation of delamination in composite laminates under fatigue loads. The numerical tool FT‐SMXB, based on the Paris Law and virtual crack closure technique, for the mimic of fatigue‐driven delamination, has been integrated with a user material subroutine, based on the generalized residual material property 7degradation model and the Hashin fatigue failure criteria. Typical aeronautical stiffened panel has been considered as test case. Matrix damages and strength degradation due to fatigue cycles have been found to influence the propagation of delamination. Highlights: Interaction between interlaminar/intralaminar damages on the fatigue behavior of laminates. Development of a UserMat to simulate the degradation of material properties. Assessment of the fatigue and post‐fatigue behavior of a composite stiffened panel. Study of the boundary conditions and crack length influence on the damage evolution.